Nicotinamide phosphoribosyltransferase production in human spermatozoa is influenced by maturation stage. (27th August 2016) - Riammer, S.; Garten, A.; Schaab, M.; Grunewald, S.; Kiess, W.; Kratzsch, J.; Paasch, U.
Summary: High amounts of nicotinamide phosphoribosyltransferase (NAMPT) were found in human seminal plasma. This enzyme influences energy metabolism and apoptosis and is essential for the regulation of cellular nicotinamide adenine dinucleotide (NAD) + levels in somatic cells. NAD + is required as a co‐substrate for dehydrogenases, which are potentially important for spermatogenesis. The functional significance of intra‐ and extracellular NAMPT in human reproduction, however, has not been defined yet. The objectives of the study were therefore to determine NAMPT protein expression in human spermatozoa and testes, the secretion of NAMPT by spermatozoa depending on their maturation stage and the impact of NAMPT enzymatic function on sperm viability, motility, fertilisation capacity and induction of apoptosis. Firstly, we detected NAMPT protein in different cell types of human testes. NAMPT protein was also detected in spermatozoa, with significantly higher amounts in immature than in mature ejaculated spermatozoa. Additionally, NAD + levels were significantly higher in immature than in mature spermatozoa. Secondly, NAMPT was released into the supernatant of human spermatozoa, with significantly higher NAMPT levels in supernatant of immature spermatozoa compared with mature cells. Finally, the specific inhibition of the enzyme by FK866 did not influence motility, capacitation or apoptosis signalling. In summary, NAMPT is produced in human spermatozoa in a maturation‐dependent manner.